The Effect of Debt-to-Equity Ratio and Firm Size on Stock Price Volatility - Juniansah, Rayhan; Abdurohim, Abdurohim (LifeSciFi, 2026)
The LQ45 index consists of blue-chip stocks known for their significant market capitalization and high liquidity. Despite this, during the 2020–2024 timeframe, stock price fluctuations within this index stayed notably high and, at some points, even exceeded the volatility of the Composite Stock Price Index (IHSG), indicating persistent uncertainty and risk in the market. This study seeks to investigate how the debt-to-equity ratio and the size of a firm influence the variations in stock prices of companies listed in the LQ45 index on the Indonesia Stock Exchange. A quantitative research methodology was utilized, relying on secondary data sourced from corporate financial reports and historical stock price data. The study included 24 companies chosen via purposive sampling, and the analysis was conducted using panel data regression in EViews 12. The results show that the debt-to-equity ratio positively and significantly affects stock price volatility, while firm size negatively and significantly impacts stock price volatility. These findings imply that investors and corporate managers should prioritize prudent capital structure management and firm size considerations to mitigate stock price volatility, while future research should incorporate broader samples and additional financial and macroeconomic variables to enhance generalizability and explanatory power.